2008
DOI: 10.1007/s12262-008-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal scar endometriosis

Abstract: Although scar endometriosis is a rare entity, a good and diligent surgical history and a high index of suspicion are the keys for a pre-operative diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
2
3
0
3
Order By: Relevance
“…In this study, the average age at presentation was 30 years as observed by others authors 1, 2, 8, 14–16. An increase in the dimensions of the tumor, accompanied by increasing colicky‐like pain during the menstrual period, leads to suspect endometriosis 16.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this study, the average age at presentation was 30 years as observed by others authors 1, 2, 8, 14–16. An increase in the dimensions of the tumor, accompanied by increasing colicky‐like pain during the menstrual period, leads to suspect endometriosis 16.…”
Section: Discussionsupporting
confidence: 70%
“…It is important to make the differential diagnosis with abdominal wall tumors (lipoma, sarcoma, and metastasis), hematoma, abscess, keloid, and hypertrophic scar 15. Imaging techniques are nonspecific and needle biopsy may confirm the diagnosis 2, 13, 22–25.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis should be considered in differential diagnosis of a painful mass in anterior abdominal wall, especially in women with a history of pelvic or obstetric surgery. According to our findings and the literature (2,4,(6)(7)(8)(9)(10)(11)(12)(13)(14)24,25), previous cesarean section is the most well known risk factor in etiology. This suggests that the disease is highly caused by iatrogenic sowing.…”
Section: Resultssupporting
confidence: 67%
“…None of these theories can exactly explain the whole case. Therefore, some researchers claim that genetic and environmental factors together play a role in the etiology of endometriosis (11). Cesarean section is one of the most common causes of AWE (2,6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation